2009
DOI: 10.1016/j.biomaterials.2009.07.049
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial vertical bone augmentation: A comparison between 3D printed monolithic monetite blocks and autologous onlay grafts in the rabbit

Abstract: a b s t r a c tOnlay autografting is amongst the most predictable techniques for craniofacial vertical bone augmentation, however, complications related to donor site surgery are common and synthetic alternatives to onlay autografts are desirable. Recent studies have shown that the acidic calcium phosphates, brushite and monetite, are osteoconductive, osteinductive and resorb faster in vivo than hydroxyapatite. Moreover, they can be 3D printed allowing precise host bone-implant specific conformation. The objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
108
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(120 citation statements)
references
References 36 publications
9
108
0
3
Order By: Relevance
“…Cer tain ceramic phases such as monetite, brushite and bTCP, have in previous studies shown convincing osteoconduc tive properties, and for monetite, osteoinductive proper ties, and may be preferred choices for use in bone repair. 7,22 Conversely, these ceramic materials may resorb too quick ly to allow for desired coupled bone formation. The ad dition of bPPi may be critical for prolonging resorption rate, allowing sufficient time for coupled bone formation to occur, and thereby realizing the implant's potential for bioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Cer tain ceramic phases such as monetite, brushite and bTCP, have in previous studies shown convincing osteoconduc tive properties, and for monetite, osteoinductive proper ties, and may be preferred choices for use in bone repair. 7,22 Conversely, these ceramic materials may resorb too quick ly to allow for desired coupled bone formation. The ad dition of bPPi may be critical for prolonging resorption rate, allowing sufficient time for coupled bone formation to occur, and thereby realizing the implant's potential for bioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they can be resorbed and rapidly in-situ be replaced by new bone, resulting in directly fixing to bone surfaces. Thus, monetite shows its potential as a bone regeneration material [13][14][15]. However, the mechanical strength properties of monetite ceramics are poorer than those of natural bone, limiting their applications in load-bearing sites.…”
Section: Introductionmentioning
confidence: 98%
“…Precipitation of these phases occurs and nano-and micrometer sized crystals are formed. Both apatite and brushite systems have been successful in vivo, (Turner et al, 2008;Apelt et al, 2004;Tamimi et al, 2009a) and in clinical studies (Ryf et al, 2009;Larsson and Bauer, 2002) and there are several commercial products on the market intended for various orthopaedic applications . However, there are still properties that can be improved for the CPCs.…”
Section: Introductionmentioning
confidence: 98%